(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In this article, the role of tuyugh as a genre, which has an important place in Uzbek literature, is analyzed on a scientific and theoretical basis. The similarities and differences between rubai and qit’a are highlighted, and the unique poetic features of tuyugh are revealed. In the study, the inter-genre transformation of tuyugh is also analyzed in detail.